High-performance corrosion-resistant coating material and preparation method thereof

A high-performance corrosion-resistant coating material with specific formulations addresses the issue of peeling and cracking in harsh environments by minimizing stress concentration and ensuring uniform adhesion, offering robust protection and industrial applicability.

CN119177049APending Publication Date: 2024-12-24TANGSHAN COLLEGE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411464428.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Traditional corrosion-resistant coating materials fail to maintain integrity in complex and harsh environments, leading to peeling, cracking, and substrate corrosion due to stress alternation and uneven stress distribution.

Method used

A high-performance corrosion-resistant coating material composed of fluorocarbon resin, organosilicon micropowder, curing agent, dispersant, and additives like carboxylic acid rare earth salts and carbon nanotubes, formulated to minimize stress concentration and maintain uniform adhesion with the substrate.

Benefits of technology

The coating exhibits strong corrosion resistance, weather resistance, and mechanical properties, maintaining adhesion and preventing cracking even in harsh conditions, with a simple preparation method suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092875790000191
    Figure BDA0005092875790000191
  • Figure BDA0005092875790000201
    Figure BDA0005092875790000201
  • Figure BDA0005092875790000211
    Figure BDA0005092875790000211
Patent Text Reader

Abstract

The invention provides a high-performance corrosion-resistant coating material and a preparation method thereof, and relates to the field of coating materials, fluorocarbon resin, organic silicon micro powder and a curing agent are configured according to a reasonable proportion, so that the coating material not only has extremely high corrosion resistance, but also has good weather resistance and wear resistance; the dispersing agent is reasonably prepared, so that the coating material has a uniform internal structure, the structure stress during coating formation is further reduced to the maximum extent, and the situation that the coating material causes local stress concentration in a complex environment, overall stress distribution is uneven, and consequently, the coating cracks or falls off is avoided; through reasonable configuration of other additives, the alternating stress resistance of the coating material is improved, and meanwhile, the interface between the coating material and a base material is difficult to form relatively large interface stress in a complex and changeable environment, so that the strong adhesive force between the coating material and the base material is continuously maintained, and the service life of the coating material is prolonged. And the damage of the coating and the failure of the corrosion resistance are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coating materials, and in particular to a high-performance corrosion-resistant coating material and a preparation method thereof. Background Art

[0002] With the continuous development of industrial technology, the requirements for material corrosion resistance are increasing. Traditional coating materials often have problems such as peeling and cracking in complex environments, which leads to corrosion of the substrate and shortens its service life.

[0003] It should be further explained that the reason why traditional corrosion-resistant coating materials are prone to peeling and cracking, which eventually leads to corrosion of the substrate, is mainly because they cannot serve for a long time in a variety of complex and changeable environments, especially in a variety of harsh environments (such as seawater, strong acids, strong alkalis and other corrosive media, as well as high temperature and high pressure or extremely low temperature and low pressure). Traditional corrosion-resistant coating materials are prone to stress alternation, resulting in uneven distribution of interface stress between the coating material and the substrate, which in turn causes local stress concentration and / or local stress release, and then the coating material will soon crack and peel, causing the substrate to be corroded by the corrosive medium. Therefore, it is of great significance to develop a corrosion-resistant coating material that can exhibit high performance and long life in various complex and harsh environments. Summary of the invention

[0004] The object of the present invention is to provide a high-performance corrosion-resistant coating material and a preparation method thereof, which is intended to overcome the above-mentioned problems existing in the prior art.

[0005] The present invention solves the technical problem by adopting the following technical solutions.

[0006] The present invention provides a high-performance corrosion-resistant coating material, which is made of a variety of raw materials, and the various raw materials include, by weight:

[0007] Fluorocarbon resin 90-110 parts;

[0008] 5-19 parts of organosilicon micropowder;

[0009] 10-20 parts of curing agent;

[0010] 9-18 parts of dispersant; and

[0011] 14-39 parts of other additives;

[0012] Wherein, the curing agent includes at least one of epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride;

[0013] The dispersant includes at least one of xanthan gum, polyacrylamide, alkali metal phosphate and silicate;

[0014] The other additives include carboxylic acid rare earth salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate and basalt fibers.

[0015] Further, in a preferred embodiment of the present invention, the curing agent includes the epoxy resin curing agent, the aromatic amine curing agent, the polyether amine curing agent, the lime, the lithium silicate and the calcium chloride;

[0016] The dispersant includes the xanthan gum, the polyacrylamide, the alkali metal phosphate and the silicate.

[0017] Furthermore, in a preferred embodiment of the present invention, the carboxylic acid rare earth salt, the carbon nanotubes, the titanium dioxide, the oxidized polyethylene wax, the sodium tungstate and the basalt fiber are in a mass ratio of 4:3:2:2:3:2.

[0018] Furthermore, in a preferred embodiment of the present invention, the plurality of raw materials are made of the following raw materials in parts by weight:

[0019] 94-102 parts of fluorocarbon resin;

[0020] 7-16 parts of organic silicon micropowder;

[0021] 12-19 parts of curing agent;

[0022] 10-16 parts of dispersant; and

[0023] Other additives 16-32 parts.

[0024] Further, in a preferred embodiment of the present invention, the weight portion of the curing agent is 18 parts, and the curing agent comprises, by weight:

[0025] 4 parts of the epoxy resin curing agent;

[0026] 4 parts of the aromatic amine curing agent;

[0027] 2 parts of the polyetheramine curing agent;

[0028] 2 parts of lime;

[0029] 3 parts of the lithium silicate; and

[0030] Described calcium chloride 3 parts.

[0031] Further, in a preferred embodiment of the present invention, the weight portion of the dispersant is 14 parts, and the dispersant comprises, by weight:

[0032] 4 parts of xanthan gum;

[0033] 5 parts of the polyacrylamide;

[0034] 2 parts of the alkali metal phosphate; and

[0035] 3 parts of the silicate.

[0036] Further, in a preferred embodiment of the present invention, the weight portion of the other additives in the plurality of raw materials is 16 parts;

[0037] The epoxy resin curing agent is an isocyanate curing agent, and the aromatic amine curing agent is m-phenylenediamine;

[0038] The alkali metal phosphate is sodium pyrophosphate, and the silicate is water glass;

[0039] The carboxylic acid rare earth salt is a stearic acid rare earth salt, an isooctanoic acid rare earth salt or / and a cyclohexane acid rare earth salt.

[0040] Furthermore, in a preferred embodiment of the present invention, the other additives also include lanthanum nitrate, stannous sulfate and ethyl acetate;

[0041] The carboxylic acid rare earth salt, the carbon nanotubes, the titanium dioxide, the oxidized polyethylene wax, the sodium tungstate, the basalt fiber, the lanthanum nitrate and the stannous sulfate and the ethyl acetate in the other additives are in a weight ratio of 4:3:2:2:3:2:4:3:9.

[0042] The present invention also provides a method for preparing a high-performance corrosion-resistant coating material, which comprises the following steps:

[0043] By weight, 5-19 parts of organosilicon powder and 10-20 parts of curing agent are added to 9 parts of diluent and stirred at a first speed to obtain a diluent;

[0044] Adding 90-110 parts of fluorocarbon resin, 14-39 parts of other additives and 9-18 parts of dispersant into the diluent and stirring at a second speed to obtain a slurry of high-performance corrosion-resistant coating material;

[0045] Immersing the pretreated substrate into the slurry for coating, and then drying the coated substrate at room temperature for 72 hours;

[0046] Among them, the curing agent includes at least one of epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride; the dispersant includes at least one of xanthan gum, polyacrylamide, alkali metal phosphate and silicate; the other additives include carboxylic acid rare earth salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate and basalt fiber.

[0047] Further, in a preferred embodiment of the present invention, when 90-110 parts of the fluorocarbon resin, 14-39 parts of the other additives and 9-18 parts of the dispersant are added to the diluent, the order of addition is first adding the dispersant to the diluent and stirring, and then adding the fluorocarbon resin and the other additives in sequence and stirring;

[0048] The curing agent includes epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride; the dispersant includes xanthan gum, polyacrylamide, alkali metal phosphate and silicate; the other additives also include lanthanum nitrate and stannous sulfate;

[0049] In the preparation method of the high-performance corrosion-resistant coating material, the first speed stirring and the second speed stirring are both continuous and uninterrupted stirring, the stirring speed of the first speed stirring is 400-600rpm, and the stirring speed of the second speed stirring is 800-1200rpm.

[0050] The beneficial effects of a high-performance corrosion-resistant coating material and a preparation method thereof according to an embodiment of the present invention are:

[0051] By configuring the fluorocarbon resin, organosilicon powder and curing agent in a reasonable proportion, the coating material not only has extremely strong corrosion resistance, but also has good weather resistance, wear resistance and comprehensive mechanical properties; by configuring the dispersant in the fluorocarbon resin, organosilicon powder and curing agent reasonably, the coating material has high corrosion resistance and uniform internal structure, thereby minimizing the tissue stress during coating formation, avoiding the coating material from inducing local stress concentration in a complex environment, causing uneven overall stress distribution, and ultimately causing the coating to crack or fall off; by the reasonable configuration of other additives, not only the corrosion resistance of the coating material is further improved, but also the strength and toughness of the coating material are well balanced, and its ability to resist alternating stress is improved. At the same time, it is also difficult for the interface between the coating material and the substrate to form a large interface stress in a complex and changeable environment, thereby continuously maintaining a strong adhesion between the coating material and the substrate, avoiding the destruction of the coating and the failure of corrosion resistance; in addition, the preparation method of the above-mentioned high-performance corrosion-resistant coating material provided in the embodiment of the present invention has a simple process, can efficiently prepare the above-mentioned high-performance corrosion-resistant coating material, and is convenient for industrial production and promotion. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0053] The high performance corrosion resistant coating material and the preparation method thereof according to the embodiment of the present invention are described in detail below.

[0054] The embodiment of the present invention provides a high-performance corrosion-resistant coating material, which is made of a variety of raw materials, which include, by weight: 90-110 parts of fluorocarbon resin, 5-19 parts of organosilicon powder, 10-20 parts of curing agent, 9-18 parts of dispersant and 14-39 parts of other additives. Preferably, in a preferred embodiment of the present invention, the various raw materials include, by weight: 94-102 parts of fluorocarbon resin, 7-16 parts of organosilicon powder, 12-19 parts of curing agent, 10-16 parts of dispersant and 16-32 parts of other additives.

[0055] Further, the curing agent optionally includes at least one of epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride. Preferably, the curing agent includes epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride; more specifically and preferably, the epoxy resin curing agent is an isocyanate curing agent and the aromatic amine curing agent is m-phenylenediamine. It should be noted that the corrosion-resistant coating material provided in the embodiment of the present invention is configured in a preferred proportion as fluorocarbon resin, silicone powder and a curing agent including epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride. This is because firstly, the fluorocarbon resin, silicone powder and curing agent are configured in a reasonable proportion so that different curing agents can play a synergistic role (the six curing agents, epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride, play a synergistic effect, so that the fluorocarbon resin and silicone powder are cross-linked more fully and densely), so that the coating material not only has extremely strong corrosion resistance and waterproofness, but also has good weather resistance and wear resistance as well as comprehensive mechanical properties; secondly, it should be specifically noted that the three organic curing agents, epoxy resin curing agent, aromatic amine curing agent and polyether amine curing agent, are synergistically cross-linked to make the corrosion-resistant coating material It has high elasticity and adhesion as well as excellent heat resistance and chemical corrosion resistance; and the three organic curing agents, epoxy resin curing agent, aromatic amine curing agent and polyether amine curing agent, are compounded with the three inorganic curing agents, lime, lithium silicate and calcium chloride, showing a 1+1>2 improvement in curing performance; in addition, fluorocarbon resin has a strong CF bond as the skeleton and good crystallinity, so it has the characteristics of non-adhesion, non-wettability, low-temperature flexibility, weather resistance (heat resistance and cold resistance) and chemical resistance. Silicone micropowder is an aggregate of extremely small silica particles, usually with a particle size range of 0.1 microns to tens of microns, with the characteristics of high purity, high dispersibility, low oil absorption rate, etc. It not only improves the material uniformity of the coating material (reduces the residual stress and stress concentration inside the organizational structure), but also reduces the possibility and ratio of energy and / or material exchange between the coating material and the environmental medium after formation.

[0056] Further optionally, the above-mentioned dispersant includes at least one of xanthan gum, polyacrylamide, alkali metal phosphate and silicate. Preferably, the dispersant includes the xanthan gum, the polyacrylamide, the alkali metal phosphate and the silicate, and more preferably, the alkali metal phosphate is sodium pyrophosphate, and the silicate is water glass. It should be noted that by rationally configuring the dispersant including xanthan gum, polyacrylamide, alkali metal phosphate and silicate in the fluorocarbon resin, the organosilicon powder and the curing agent, the coating material has a uniform internal structure while having high corrosion resistance, thereby minimizing the tissue stress during coating formation, avoiding the coating material from inducing local stress concentration in a complex environment, causing uneven overall stress distribution, and ultimately leading to the problem of coating cracking or falling off. Specifically, the two inorganic dispersants, alkali metal phosphates and silicates, are rationally compounded with the two organic dispersants, xanthan gum and polyacrylamide, which have the following four effects: First, improving the dispersion effect: the synergistic effect of the components in the composite dispersant can effectively improve the dispersion effect of solid particles in liquids or semi-solids, making the particle distribution more uniform; second, enhancing the stability of the system: by reducing the surface tension of the suspension, the wetting properties of the solid particles are improved, and flocculation and sedimentation are reduced, thereby enhancing the dynamic stability of the suspension; third, optimizing the processing performance: the composite dispersant can improve the processing performance of the coating, such as improving the viscoelasticity and surface finish of the coating; fourth, broadening the scope of environmental use and improving the adaptability to complex environments: the comprehensive performance of the composite dispersant makes its coating material have a wide range of application potential under conditions such as seawater, strong acid, strong alkali, high temperature and high pressure, and extremely low temperature and low pressure, and can meet the use requirements in different harsh environments.

[0057] Further optionally, in some embodiments of the present invention, the other additives include carboxylic acid rare earth salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate and basalt fibers. Preferably, the carboxylic acid rare earth salts, the carbon nanotubes, the titanium dioxide, the oxidized polyethylene wax, the sodium tungstate and the basalt fibers are in a mass ratio of 4:3:2:2:3:2. It should be noted that by reasonably configuring other additives in the coating material, not only the corrosion resistance of the coating material is further improved, but also the strength and toughness of the coating material are well balanced, and its ability to resist alternating stress is improved. At the same time, it also makes it difficult for the interface between the coating material and the substrate to form a large interface stress in a complex and changeable environment, thereby continuously maintaining a strong adhesion between the coating material and the substrate, avoiding damage to the coating and failure of corrosion resistance.

[0058] Further preferably, the carboxylic acid rare earth salt is a stearic acid rare earth salt, an isooctanoic acid rare earth salt or / and a cyclohexane acid rare earth salt; in addition, the other additives also include lanthanum nitrate, stannous sulfate and ethyl acetate, and more preferably, the carboxylic acid rare earth salt, the carbon nanotubes, the titanium dioxide, the oxidized polyethylene wax, the sodium tungstate, the basalt fiber, the lanthanum nitrate, the stannous sulfate and the ethyl acetate in the other additives are in a weight ratio of 4:3:2:2:3:2:4:3:9. It should be noted that ethyl acetate, as a diluent, mainly plays a role in adjusting the viscosity and fluidity of the coating. It can help adjust the viscosity of the coating and improve the fluidity of the coating by effectively dissolving many organic substances. In addition, compared with some other organic solvents, ethyl acetate has lower toxicity, is relatively safe to use, and can be biodegraded, with less impact on the environment. It should be emphasized that by preferably configuring the material selection of other additives and limiting the relative proportion, the following five functions and effects can be specifically achieved in the coating: First, drying effect: carboxylic acid rare earth salts as drying agents can accelerate the drying film-forming process of drying oils in the coating, improve the curing speed of the coating and uniform stress release; Second, enhance mechanical properties: the addition of carbon nanotubes and basalt fibers can significantly improve the toughness and strength of the coating, and enhance the impact resistance and wear resistance of the coating; Third, improve anti-corrosion performance: titanium dioxide and oxidized polyethylene wax have good corrosion resistance, can effectively isolate air and moisture, and improve the anti-corrosion ability of the coating; Fourth, improve weather resistance: the addition of sodium tungstate and lanthanum nitrate can enhance the weather resistance of the coating, so that the coating can maintain stable performance even in harsh environments; Fifth, optimize the comprehensive performance of the coating: stannous sulfate as an additive can synergize with other ingredients to further optimize the leveling, adhesion and gloss of the coating, so that the corrosion-resistant coating material of the present application has a strong environmental adaptability and can be widely used in various complex and harsh environments.

[0059] Furthermore, in a preferred embodiment of the present invention, the weight portion of the above-mentioned curing agent is 18 parts, and the curing agent includes, by weight: 4 parts of the epoxy resin curing agent, 4 parts of the aromatic amine curing agent, 2 parts of the polyether amine curing agent, 2 parts of the lime, 3 parts of the lithium silicate and 3 parts of the calcium chloride.

[0060] Furthermore, in a preferred embodiment of the present invention, the weight portion of the above-mentioned dispersant is 14 parts, and the dispersant comprises, by weight: 4 parts of the xanthan gum, 5 parts of the polyacrylamide, 2 parts of the alkali metal phosphate and 3 parts of the silicate, and preferably, the weight portion of the other additives among the multiple raw materials is 16 parts.

[0061] The embodiment of the present invention also provides a method for preparing a high-performance corrosion-resistant coating material. The preparation process is simple and can efficiently prepare the high-performance corrosion-resistant coating material, which is convenient for industrial production and promotion. The method specifically includes the following steps:

[0062] S1. By weight, 5-19 parts of organosilicon powder and 10-20 parts of curing agent are added to 9 parts of diluent and stirred at a first speed to obtain a diluent; wherein the curing agent includes one or more of epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride; and the diluent is ethyl acetate.

[0063] S2, adding 90-110 parts of fluorocarbon resin, 14-39 parts of other additives and 9-18 parts of dispersant to the diluent and stirring at a second speed to obtain a slurry of high-performance corrosion-resistant coating material; wherein the dispersant includes one or more of xanthan gum, polyacrylamide, alkali metal phosphate and silicate, and other additives include carboxylic acid rare earth salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate and basalt fiber, and preferably, other additives also include lanthanum nitrate and stannous sulfate. In addition, it should be noted that when 90-110 parts of the fluorocarbon resin, 14-39 parts of the other additives and 9-18 parts of the dispersant are added to the diluent, the order of addition is to first add the dispersant to the diluent for stirring, and then add the fluorocarbon resin and other additives in sequence for stirring. It should be emphasized that the reason for adding various components in the specific order defined above is to ensure that each component fully plays its role in the coating, avoid mutual interference or influence, and the sequential operation can also improve the overall stability and uniformity of the coating, thereby improving the coating effect and service life. Specifically, the dispersant is first added to the diluent, which can quickly disperse and wet the solid particles, reduce their surface tension, and improve the uniformity of the particles in the liquid. The dispersant can also prevent the particles from reaggregating, thereby maintaining the stability of the suspension. In addition, after the dispersant and the diluent are fully mixed, the fluorocarbon resin and other additives are added to ensure that the resin particles are evenly distributed in the coating, which is beneficial to bring into play the weather resistance, chemical resistance and corrosion resistance of the fluorocarbon resin and the related performance effects of other additives, thereby improving the overall performance of the coating.

[0064] In addition, it should be emphasized that in the embodiment of the present invention, when preparing the above-mentioned high-performance corrosion-resistant coating material, the first speed stirring and the second speed stirring are both continuous and uninterrupted stirring, the stirring speed of the first speed stirring is 400-600rpm, and the stirring speed of the second speed stirring is 800-1200rpm. It should be noted that continuous and uninterrupted stirring is to prevent precipitation and mixing more fully and evenly, and the stirring speed of the first speed stirring and the second speed stirring is limited because the stirring speed is too large or too small, which is not conducive to the full mixing of different components. If the stirring speed is too low, not only the mixing is not sufficient and easy to precipitate, but also time-consuming, especially the specific surface area of ​​various components per unit volume is smaller, which is not conducive to the performance of different components; and the stirring speed is too high, which will not only cause material splashing or destroy the formed structure, such as floccules, thereby reducing the treatment effect or product quality, but also may cause the system temperature to be too high, affecting the coating material result or quality. In addition, the stirring speed of the second speed stirring is greater than the stirring speed of the first speed stirring, because the components of the mixing environment of the second speed stirring are more diverse and complex, and a higher speed is required to maintain the homogenization and stabilization of the entire coating mixing system.

[0065] S3, immersing the pretreated substrate into the above slurry for coating, and then drying the coated substrate at room temperature for 72 hours, a high-performance corrosion-resistant coating can be obtained on the substrate. It should be noted that the preparation method of the above-mentioned high-performance corrosion-resistant coating material provided in the embodiment of the present invention is not only simple in process, but also can efficiently prepare the above-mentioned high-performance corrosion-resistant coating material, which is very convenient for industrial production and promotion, and has broad market application prospects.

[0066] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0067] Example 1

[0068] The present embodiment provides a high-performance corrosion-resistant coating material, which is made of a variety of raw materials, which include, by weight: 100g of fluorocarbon resin, 12g of organic silicon powder, 18g of curing agent, 14g of dispersant and 32g of other additives. Specifically, the curing agent is 4g of epoxy resin curing agent, 4g of aromatic amine curing agent, 2g of polyether amine curing agent, 2g of lime, 3g of lithium silicate and 3 parts of calcium chloride, and optionally, the epoxy resin curing agent is an isocyanate curing agent and the aromatic amine curing agent is m-phenylenediamine. In addition, the dispersant is specifically xanthan gum 4g, polyacrylamide 5g, alkali metal phosphate 2g and silicate 3g; other additives are specifically carboxylic acid rare earth salt 4g, carbon nanotube 3g, titanium dioxide 2g, oxidized polyethylene wax 2g, sodium tungstate 3g, basalt fiber 2g, 4g of lanthanum nitrate and 3g of stannous sulfate and 9g of ethyl acetate. It should be noted that, the alkali metal phosphate is sodium pyrophosphate, the silicate is water glass, and the carboxylic acid rare earth salt is stearic acid rare earth salt, isooctanoic acid rare earth salt and cyclohexane acid rare earth salt.

[0069] This embodiment also provides a method for preparing the above-mentioned high-performance corrosion-resistant coating material, which comprises the following steps:

[0070] S1. In parts by weight, 12 g of organosilicon powder and 18 g of curing agent are added to 9 g of diluent and stirred at a first speed to obtain a diluent; wherein the curing agent includes epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride, and the diluent is ethyl acetate, and the specific weight ratio is weighted according to the specific formula of the high performance corrosion-resistant coating material provided above in this embodiment.

[0071] S2. 14g of dispersant, 100g of fluorocarbon resin and 32g of other additives are sequentially added to the diluent and stirred at a second speed to obtain a slurry of high-performance corrosion-resistant coating material; wherein the dispersant includes xanthan gum, polyacrylamide, alkali metal phosphate and silicate, and other additives include carboxylic acid rare earth salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate, basalt fiber, lanthanum nitrate and stannous sulfate, and the specific weight ratio is, for example, the specific formula of the high-performance corrosion-resistant coating material provided above in this embodiment. In addition, it should be noted that when preparing the above-mentioned high-performance corrosion-resistant coating material, the above-mentioned first speed stirring and second speed stirring are both continuous and uninterrupted stirring, and the stirring speed of the first speed stirring is 500rpm, and the stirring speed of the second speed stirring is 1000rpm.

[0072] S3. Immerse the pretreated substrate into the above slurry for coating, and then dry the coated substrate at room temperature for 72 hours to obtain a high-performance corrosion-resistant coating on the substrate.

[0073] Example 2

[0074] The high-performance corrosion-resistant coating material and preparation method provided in this embodiment are substantially the same as those in embodiment 1, except that the raw materials in this embodiment include 90g of fluorocarbon resin, 5g of organosilicon powder, 10g of curing agent, 9g of dispersing agent and 14g of other additives. It should be noted that the corresponding specific components in the curing agent, dispersing agent and other additives are the same as those in embodiment 1, and the specific mass of each component can be adaptively adjusted according to the mass ratio of the components in embodiment 1. For example, the mass of the epoxy resin curing agent in the curing agent of this embodiment is 4*10 / 18=2.22g, and the mass of other corresponding components is similar, and the subsequent related embodiments will not be given examples for further description.

[0075] Example 3

[0076] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in embodiment 1, except that the raw materials in this embodiment include 94 g of fluorocarbon resin, 7 g of organosilicon powder, 12 g of curing agent, 10 g of dispersing agent and 16 g of other additives. It should be noted that the corresponding specific components of the curing agent, dispersing agent and other additives are the same as those in embodiment 1, and the specific mass of each component can be adaptively adjusted according to the mass ratio of the components in embodiment 1.

[0077] Example 4

[0078] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in embodiment 1, except that, in the raw materials of this embodiment, 110 g of fluorocarbon resin, 19 g of organosilicon powder, 20 g of curing agent, 18 g of dispersant and 39 g of other additives are included. It should be noted that the corresponding specific components of the curing agent, dispersant and other additives are the same as those in embodiment 1, and the specific mass of each component can be adaptively adjusted according to the mass ratio of the components in embodiment 1.

[0079] Example 5

[0080] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that the raw materials in this embodiment include 102 g of fluorocarbon resin, 16 g of organosilicon powder, 19 g of curing agent, 16 g of dispersing agent and 32 g of other additives. It should be noted that the corresponding specific components of the curing agent, dispersing agent and other additives are the same as those in Example 1, and the specific mass of each component can be adaptively adjusted according to the mass ratio of the components in Example 1.

[0081] Example 6

[0082] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that, among the raw materials in this embodiment, the curing agent component is only epoxy resin curing agent.

[0083] Example 7

[0084] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that, among the raw materials in this embodiment, the curing agent component is only a polyetheramine curing agent.

[0085] Example 8

[0086] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only two components, namely aromatic amine curing agent and lime, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0087] Example 9

[0088] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only two components, namely, polyetheramine curing agent and lithium silicate, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0089] Example 10

[0090] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only three components: epoxy resin curing agent, polyether amine curing agent and lithium silicate, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0091] Embodiment 11

[0092] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only three components: epoxy resin curing agent, calcium chloride and lithium silicate, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0093] Example 12

[0094] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only four components: epoxy resin curing agent, polyether amine curing agent, lithium silicate and calcium chloride, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0095] Embodiment 13

[0096] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only four components: epoxy resin curing agent, polyether amine curing agent, lime and lithium silicate, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0097] Embodiment 14

[0098] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only five components, namely, epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime and lithium silicate, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0099] Embodiment 15

[0100] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the curing agent comprises only five components: epoxy resin curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0101] Example 16

[0102] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that, among the raw materials in this embodiment, the dispersant component is only xanthan gum.

[0103] Embodiment 17

[0104] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that, among the raw materials in this embodiment, the dispersant component is only polyacrylamide.

[0105] Embodiment 18

[0106] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that among the raw materials in this embodiment, the dispersant components include only two types, xanthan gum and alkali metal phosphate, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Example 1.

[0107] Embodiment 19

[0108] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that among the raw materials in this embodiment, the dispersant components include only two types, xanthan gum and silicate, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Example 1.

[0109] Embodiment 20

[0110] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Embodiment 1, except that among the raw materials in this embodiment, the other additives include only six kinds of rare earth carboxylate salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate and basalt fibers, and the corresponding masses can be adaptively adjusted according to the mass ratio of the components in Embodiment 1.

[0111] Embodiment 21

[0112] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that, among the raw materials in this embodiment, the carboxylic acid rare earth salt is only one type of stearic acid rare earth salt.

[0113] Embodiment 22

[0114] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that, among the raw materials in this embodiment, the carboxylic acid rare earth salts include only two types: stearic acid rare earth salt and cyclohexane acid rare earth salt.

[0115] Embodiment 23

[0116] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that, in the preparation method of the high-performance corrosion-resistant coating material in this embodiment, the stirring speed of the first speed stirring is 400 rpm, and the stirring speed of the second speed stirring is 800 rpm.

[0117] Embodiment 24

[0118] The high-performance corrosion-resistant coating material and preparation method thereof provided in this embodiment are substantially the same as those in Example 1, except that, in the preparation method of the high-performance corrosion-resistant coating material in this embodiment, the stirring speed of the first speed stirring is 600 rpm, and the stirring speed of the second speed stirring is 1200 rpm.

[0119] Comparative Example

[0120] A common GH102 type white epoxy ceramic coating on the market was made into a comparative sample, and prepared to be compared with Examples 1-24 as a test example.

[0121] Test example

[0122] First, the above-mentioned embodiments 1-24 and comparative examples were subjected to corrosion resistance tests under the same conditions for diversified environmental changes. It should be noted that during the corrosion resistance test, 25 samples were first immersed in a 6% NaCl solution for 168 hours, and then the 25 samples were moved to a hydrochloric acid solution with a pH of 4 and immersed for 72 hours, and finally 25 samples were moved to a sodium hydroxide alkaline solution with a pH of 10 and immersed for 72 hours, and then all samples were taken out, and the above 25 samples were placed in an extreme environment for performance testing: Specifically, the sample was first placed in a high and low temperature alternating test box and pressurized to 1.5 atmospheres and heated to 120 degrees Celsius, and kept for 12 hours, and then the high and low temperature alternating test box was adjusted to 0.6 atmospheres and cooled to minus 10 degrees Celsius, and kept for 12 hours, and finally the pressure was released to restore to room temperature, and 25 test samples were taken out for observation after rinsing, weight loss corrosion resistance performance was calculated, and impact resistance mechanical performance tests were performed, and the obtained data results are shown in Table 1.

[0123] Table 1 Test results of corrosion resistance and impact resistance

[0124]

[0125]

[0126]

[0127]

[0128] It can be seen from Table 1 that the coating material samples of Examples 1-24 provided by the present invention in the test examples have extremely high corrosion resistance. Compared with the corrosion efficiency of the comparative example samples of 82.24%, the corrosion efficiency of the coating provided by the present application is about 99% as a whole, which can be said to have almost no obvious corrosion, showing excellent anti-corrosion performance. It can be seen from the test that after being subjected to acid, alkali, salt media and harsh environments of high temperature and high pressure and low temperature and low pressure, the coating samples of Examples 1-24 provided by the present application still maintain a good organizational structure without obvious cracking and peeling, which shows that the coating material provided by the examples of the present application has resisted the corrosion of the corrosive medium and the stress and strain caused by temperature and pressure, and this can also be seen from the stronger impact strength of the samples of Examples 1-24.

[0129] Furthermore, in order to further verify the uniformity and stability of the internal organizational stress structure of the corrosion-resistant coating material provided by the embodiment of the present invention, as well as the good electrical insulation it brings to the coating material, the applicant continued to conduct voltage resistance tests on the 25 samples that have passed the corrosion resistance test and impact resistance test. Specifically, the positive and negative poles of the voltage resistance tester are respectively connected to the two ends of the sample coating material, and the voltage is applied and gradually increased to a preset value, such as 500VDC, and the voltage increase rate does not exceed 100V / s. The voltage is kept stable and lasts for a period of time, such as 30 seconds. Observe whether the sample coating material has insulation breakdown such as arc and light during the test, and record the previous applied voltage value before the breakdown phenomenon occurs as the voltage resistance parameter; adjust the clamping position of the positive and negative poles of the voltage resistance tester at both ends of the coating material, measure the voltage resistance value again, and average the voltage resistance values ​​of the same coating material sample as the previous time, and take the average value as the final voltage resistance value of the coating material sample; the voltage resistance values ​​of the above 25 coating material samples are deduced by analogy, and the final data results are shown in Table 2:

[0130] Table 2 Withstand voltage values ​​of 25 coating material samples in the test example

[0131]

[0132] It can be seen from Table 2 that the samples of the corrosion-resistant coating materials provided in the present application have extremely high withstand voltage values, while the withstand voltage values ​​of the coating material samples of the comparative examples are only about two-thirds of those of the corrosion-resistant coating material samples of the embodiments of the present application. This further supports the data in Table 1, and indirectly indicates the good internal organizational structure of the coating material samples of the embodiments of the present application. It also proves that the good internal organizational structure and uniform stress state lay an important material organizational structure foundation for the coating materials of the present application to ensure good corrosion resistance under various harsh environmental conditions, thereby avoiding the occurrence of cracking and falling off, and ensuring that the substrate is always under the protection of the coating material.

[0133] In summary, the embodiment of the present invention provides a high-performance corrosion-resistant coating material and a preparation method thereof. By configuring fluorocarbon resin, organosilicon powder and curing agent in a reasonable proportion, the coating material not only has extremely strong corrosion resistance, but also has good weather resistance and wear resistance and comprehensive mechanical properties. By reasonably configuring dispersant in fluorocarbon resin, organosilicon powder and curing agent, the coating material has high corrosion resistance and uniform internal structure, thereby minimizing the tissue stress during coating formation, avoiding local stress concentration caused by the coating material in a complex environment, causing uneven overall stress distribution, and ultimately leading to coating tortoise. cracking or falling off; through the reasonable configuration of other additives, not only the corrosion resistance of the coating material is further improved, but also the strength and toughness of the coating material are well balanced, thereby improving its ability to resist alternating stress, and at the same time, it is difficult for the interface between the coating material and the substrate to form a large interface stress in a complex and changeable environment, thereby continuously maintaining a strong adhesion between the coating material and the substrate, avoiding damage to the coating and failure of the corrosion resistance; in addition, the method for preparing the above-mentioned high-performance corrosion-resistant coating material provided in an embodiment of the present invention has a simple process, can efficiently prepare the above-mentioned high-performance corrosion-resistant coating material, and is convenient for industrial production and promotion.

[0134] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A high performance corrosion resistant coating material, characterized in that: It is made of a variety of raw materials, which include by weight: Fluorocarbon resin 90-110 parts; 5-19 parts of organosilicon micropowder; 10-20 parts of curing agent; 9-18 parts of dispersant; and 14-39 parts of other additives; Wherein, the curing agent includes at least one of epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride; The dispersant includes at least one of xanthan gum, polyacrylamide, alkali metal phosphate and silicate; The other additives include carboxylic acid rare earth salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate and basalt fibers.

2. The high performance corrosion resistant coating material according to claim 1, characterized in that: The curing agent includes the epoxy resin curing agent, the aromatic amine curing agent, the polyether amine curing agent, the lime, the lithium silicate and the calcium chloride; The dispersant includes the xanthan gum, the polyacrylamide, the alkali metal phosphate and the silicate.

3. The high performance corrosion resistant coating material according to claim 2, characterized in that: The mass ratio of the carboxylic acid rare earth salt, the carbon nanotubes, the titanium dioxide, the oxidized polyethylene wax, the sodium tungstate and the basalt fiber is 4:3:2:2:3:

2.

4. The high performance corrosion resistant coating material according to claim 3, characterized in that: The various raw materials are made of the following raw materials in parts by weight: 94-102 parts of fluorocarbon resin; 7-16 parts of organic silicon micropowder; 12-19 parts of curing agent; 10-16 parts of dispersant; and Other additives 16-32 parts.

5. The high performance corrosion resistant coating material according to claim 4, characterized in that: The weight portion of the curing agent is 18 parts, and the curing agent includes, by weight: 4 parts of the epoxy resin curing agent; 4 parts of the aromatic amine curing agent; 2 parts of the polyetheramine curing agent; 2 parts of lime; 3 parts of the lithium silicate; and Described calcium chloride 3 parts.

6. The high performance corrosion resistant coating material according to claim 4, characterized in that: The weight portion of the dispersant is 14 parts, and the dispersant includes, by weight: 4 parts of xanthan gum; 5 parts of the polyacrylamide; 2 parts of the alkali metal phosphate; and 3 parts of the silicate.

7. The high performance corrosion resistant coating material according to claim 3, characterized in that: The weight portion of the other additives in the multiple raw materials is 16 parts; The epoxy resin curing agent is an isocyanate curing agent, and the aromatic amine curing agent is m-phenylenediamine; The alkali metal phosphate is sodium pyrophosphate, and the silicate is water glass; The carboxylic acid rare earth salt is a stearic acid rare earth salt, an isooctanoic acid rare earth salt or / and a cyclohexane acid rare earth salt.

8. The high performance corrosion resistant coating material according to claim 7, characterized in that: The other additives also include lanthanum nitrate, stannous sulfate and ethyl acetate; The carboxylic acid rare earth salt, the carbon nanotubes, the titanium dioxide, the oxidized polyethylene wax, the sodium tungstate, the basalt fiber, the lanthanum nitrate and the stannous sulfate and the ethyl acetate in the other additives are in a weight ratio of 4:3:2:2:3:2:4:3:

9.

9. A method for preparing a high-performance corrosion-resistant coating material, characterized in that: It includes the following steps: By weight, 5-19 parts of organosilicon powder and 10-20 parts of curing agent are added to 9 parts of diluent and stirred at a first speed to obtain a diluent; Adding 90-110 parts of fluorocarbon resin, 14-39 parts of other additives and 9-18 parts of dispersant into the diluent and stirring at a second speed to obtain a slurry of high-performance corrosion-resistant coating material; Immersing the pretreated substrate into the slurry for coating, and then drying the coated substrate at room temperature for 72 hours; Among them, the curing agent includes at least one of epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride; the dispersant includes at least one of xanthan gum, polyacrylamide, alkali metal phosphate and silicate; the other additives include carboxylic acid rare earth salts, carbon nanotubes, titanium dioxide, oxidized polyethylene wax, sodium tungstate and basalt fiber.

10. The method for preparing a high performance corrosion resistant coating material according to claim 9, characterized in that: When 90-110 parts of the fluorocarbon resin, 14-39 parts of the other additives and 9-18 parts of the dispersant are added to the diluent, the order of adding is first adding the dispersant to the diluent and stirring, and then sequentially adding the fluorocarbon resin and the other additives and stirring; The curing agent includes epoxy resin curing agent, aromatic amine curing agent, polyether amine curing agent, lime, lithium silicate and calcium chloride; the dispersant includes xanthan gum, polyacrylamide, alkali metal phosphate and silicate; the other additives also include lanthanum nitrate and stannous sulfate; In the preparation method of the high-performance corrosion-resistant coating material, the first speed stirring and the second speed stirring are both continuous and uninterrupted stirring, the stirring speed of the first speed stirring is 400-600rpm, and the stirring speed of the second speed stirring is 800-1200rpm.

Citation Information

Patent Citations

  • Anticorrosive jacket material of heat tracing cable and preparation method of anticorrosive jacket material

    CN106674824A

  • Composition for environment-friendly composite resin, adhesive or coating and preparation method of composition

    CN113292930A

  • Corrosion-resistant coating as well as preparation method and application thereof

    CN116715999A

  • Chemical corrosion resistant coating material and preparation method thereof

    CN117757351A

  • Polyethylene material with efficient flame retardant property and preparation method thereof

    CN117844087A